Therapeutic Potential for Cannabis and Cannabinoids - Raup-Konsavage, Wesley M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Cannabis has a history of medical use dating back millennia; however, the use of cannabis for medicinal purposes fell out of favor in the middle of the last century. There is currently a renewed interest in the potential medicinal value of this plant, as well as individual compounds produced by Cannabis (as well as synthetic analogs). Currently, nearly 50 countries permit the medical use of cannabis, and over a dozen other countries have legalized cannabis-based products (CBD, Sativex, Dronabinol, etc.) for medical use. While there exists a plethora of anecdotal reports indicating that cannabis can treat a variety of diseases, there is a limited amount of strong, evidence-based scientific data to support these claims. This Special Edition of Biomedicines, "Therapeutic Potential for Cannabis and Cannabinoids", was dedicated to providing evidence for the medicinal value of cannabis to treat human illness and disease. Topics included, but were not limited to, preclinical animal models examining the efficacy of cannabis and cannabinoid derivatives on pain, anxiety, cancer, and other diseases; and cell and molecular models of cannabinoid pharmacokinetics, drug-drug interactions, and disease treatment. These studies are of great importance not only for progressing the cannabis field, but also for validating the use of cannabis and cannabinoids as therapeutics.